Comparative toxicity of silicon dioxide, silver and iron oxide nanoparticles after repeated oral administration to rats. Issue 6 (6th March 2015) - Yun, Jun‐Won; Kim, Seung‐Hyun; You, Ji‐Ran; Kim, Woo Ho; Jang, Ja‐June; Min, Seung‐Kee; Kim, Hee Chan; Chung, Doo Hyun; Jeong, Jayoung; Kang, Byeong‐Cheol; Che, Jeong‐Hwan
Abstract: Although silicon dioxide (SiO2 ), silver (Ag) and iron oxide (Fe2 O3 ) nanoparticles are widely used in diverse applications from food to biomedicine, in vivo toxicities of these nanoparticles exposed via the oral route remain highly controversial. To examine the systemic toxicity of these nanoparticles, well‐dispersed nanoparticles were orally administered to Sprague–Dawley rats daily over a 13‐week period. Based on the results of an acute toxicity and a 14‐day repeated toxicity study, 975.9, 1030.5 and 1000 mg kg –1 were selected as the highest dose of the SiO2, Ag and Fe2 O3 nanoparticles, respectively, for the 13‐week repeated oral toxicity study. The SiO2 and Fe2 O3 nanoparticles did not induce dose‐related changes in a number of parameters associated with the systemic toxicity up to 975.9 and 1000 mg kg –1, respectively, whereas the Ag nanoparticles resulted in increases in serum alkaline phosphatase and calcium as well as lymphocyte infiltration in liver and kidney, raising the possibility of liver and kidney toxicity induced by the Ag nanoparticles. Compared with the SiO2 and Fe2 O3 nanoparticles showing no systemic distribution in all tissues tested, the Ag concentration in sampled blood and organs in the Ag nanoparticle‐treated group significantly increased with a positive and/or dose‐related trend, meaning that the systemic toxicity of the Ag nanoparticles, including liver and kidney toxicity, might be explained by extensive systemic distribution of Ag originating from the Ag nanoparticles. Our current results suggest that further study is required to identify that Ag detected outside the gastrointestinal tract were indeed a nanoparticle form or ionized form. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Although silicon dioxide (SiO2 ), silver (Ag) and iron oxide (Fe2 O3 ) nanoparticles are widely used in diverse applications from food to biomedicine, in vivo toxicities of these nanoparticles exposed via the oral route remain highly controversial. To examine the systemic toxicity of these nanoparticles, well‐dispersed nanoparticles were orally administered to Sprague–Dawley rats daily over a 13‐week period